2018
DOI: 10.5415/apallergy.2018.8.e30
|View full text |Cite
|
Sign up to set email alerts
|

Multiple food allergy - unexpected culprits

Abstract: Food allergy has an estimated prevalence of 6%–8% in children. Meat allergy and multiple food allergy due to sensitization to cross-reactive components in infancy is, however, less frequent. A 5-year-old girl was referred to our department with a multiple food allergy history. She had severe immediate worsening of her atopic dermatitis with hen's egg (6 months) and cow's milk introduction (7 months). At the age of 9 months, she presented with recurrent and reproducible atopic dermatitis' worsening and lip edem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…The grocery store or the surrounding environment might be the source of these allergies [25]. In this study, 84 % were attributable to tuna, mackerel, and codfish allergies as well as in previous studies [26,27], seafood and animals are substantial sources of allergens for dogs. Interestingly, crab/shrimp is unlikely to cause allergies (Figure 5).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The grocery store or the surrounding environment might be the source of these allergies [25]. In this study, 84 % were attributable to tuna, mackerel, and codfish allergies as well as in previous studies [26,27], seafood and animals are substantial sources of allergens for dogs. Interestingly, crab/shrimp is unlikely to cause allergies (Figure 5).…”
Section: Discussionsupporting
confidence: 65%
“…The greatest allergy levels were found in corn (28.7%) and wheat (25.0%), with peas revealing a 9.3 % allergen level (Figure 6b). Several studies [25,26] have found a significant incidence of sensitization to wheat and maize. Sensitization to meat was high in our research and numerous previously published findings (duck 24.4% and lamb 24.1%) and low in turkey (3.8%) [23,33].…”
Section: Discussionmentioning
confidence: 99%
“…Nossos resultados diferem da literatura, o qual informa que a alergia alimentar múltipla devido à sensibilização a componentes reativos na infância é menos frequente (ORNELAS et al, 2018). Uma justificativa é que determinar as estimativas da prevalência de pessoas alérgicas a vários alimentos, tende a ser dificultada porque as pessoas alérgicas a um alimento podem evitar alimentos adicionais ou podem relutar em introduzir alimentos conhecidos por alérgenos comuns (WANG, 2010).…”
Section: Resultados E Discussõesunclassified
“…Chitta et al [ 7 ] presents an article on cashew nut allergy in Singaporean children. Readers will find a rare case of multiple food allergy in infancy, where sensitization to cross-reactive components, detected by skin prick test, serum allergen specific IgE, and Immune Solid-phase Allergen Chip, was responsible for most of the children's complaints [ 8 ]. Kwak et al [ 9 ] presents a very interesting case which showed enhanced IgE responses after a tick bite from a novel Australian tick, Ixodes australiensis in a known red meat allergy patient.…”
mentioning
confidence: 99%